2014
DOI: 10.3109/00365548.2013.878034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic Bordetella pertussis and Bordetella parapertussis infections among school children in China as determined by pooled real-time PCR: A cross-sectional study

Abstract: Our results indicate that asymptomatic B. pertussis infections are common in school children in China, and asymptomatic B. parapertussis infections are more prevalent than previously documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 32 publications
2
32
2
3
Order By: Relevance
“…Many reasons for this failure to control pertussis have been proposed, including pathogen adaptation to escape vaccineinduced immunity, fast waning of immunity, especially since the switch from whole-cell to acellular vaccines (aPV), and the failure of pertussis vaccines, in particular aPV, to prevent infection and spread of B. pertussis. 5 Several investigations have now shown that apparently symptom-less B. pertussis infections are much more frequent than previously appreciated, even in fully vaccinated populations, [6][7][8][9][10] and recent modeling studies have suggested that asymptomatic transmission may be the major driver of the resurgence of pertussis. 11 In contrast to current vaccines, prior infection is able to prevent B. pertussis infection and transmission, as shown in baboon studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many reasons for this failure to control pertussis have been proposed, including pathogen adaptation to escape vaccineinduced immunity, fast waning of immunity, especially since the switch from whole-cell to acellular vaccines (aPV), and the failure of pertussis vaccines, in particular aPV, to prevent infection and spread of B. pertussis. 5 Several investigations have now shown that apparently symptom-less B. pertussis infections are much more frequent than previously appreciated, even in fully vaccinated populations, [6][7][8][9][10] and recent modeling studies have suggested that asymptomatic transmission may be the major driver of the resurgence of pertussis. 11 In contrast to current vaccines, prior infection is able to prevent B. pertussis infection and transmission, as shown in baboon studies.…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios epidemiológicos en este sentido han publicado la baja rentabilidad de hacer escrutinio sistemático a las bronquiolitis que no asocien síntomas de tosferina 16,19,20 . Se ha cuestionado el cribado sistemático de la tosferina en los pacientes con bronquiolitis no vacunados, sin clínica sugerente cuando además es posible la presencia de portadores asintomáticos de B. pertussis 17,18 . No se ha centrado nuestro trabajo en conocer la coinfección tosferina-VRS en cualquier patología respiratoria del lactante ingresado, sino solo determinar la frecuencia de coinfección por VRS en pacientes con tosferina diagnosticada y su repercusión clínica.…”
Section: Discussionunclassified
“…Esto tiene una difícil interpretación y puede tener relación con el cribado masivo de pertusis y VRS con independencia de la clínica. Es posible que la B. pertussis detectada no desarrolle necesariamente enfermedad sintomática y se trate de portadores cuya evolución dependa del estado inmunitario de la madre 17,18 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In order to approximate how many different populations in which the B. pertussis pathogen can evolve, a study similar to Zhang et al 2014 should be conducted, but with a more general population, within the United States, and possibly other countries as well. In the original study, only 629 subjects were tested, and of those, only 2 were confirmed to be infected with B. pertussis , and 1 was confirmed to be infected with B. parapertussis , when using the culture test .…”
mentioning
confidence: 99%